Rights versus obligations of persons detained in custody in Poland - Nikołajew, Jerzy (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The catalogue of rights and obligations of the persons detained in custody takes into account the constitutional prohibition to violate the human dignity. The Executive Penal Code provides for the right of a person detained in custody to notify his/her place of residence, the right of defence, the right to use food, medical and hygienic resources received outside of the pre-trial detention centre and the right to employment. On the other hand, the basic duties of the detainees included the observance of the detention centre rules and regulations as well as the cleaning works within the detention centre. However, the exercise of these powers and the enforcement of obligations are difficult to enforce, thus limiting civil liberties.